PENGARUH PENGIHAN PAJAK AKTIF DENGAN SURAT TEGURAN DAN SURAT PAKSA TERHADAP EFEKTIVITAS PENCAIRAN TUNGGAKAN PAJAK - Tania Sabrina; Siska Priyandani Yudowati; Kurnia Kurnia (Universitas Islam Negeri Alauddin Makassar, 2018)
This study aims to determine the effect of active tax collection with Warning Letter and Forced Letter either simultaneously or partially to the Effectiveness of Disbursement of Tax Arrears in KPP Pratama Majalaya. The method of analysis in this study is descriptive verification with quantitative approach in looking at the relationship between variables with the object to be examined more causal (clausal). Population and sample in this research is report of target amount and payment realization of Warning Letter and Forced Letter as well as report of target and realization of disbursement of tax arrears of 20 rtriwulan during year 2012-2016. The results showed that active tax collection with Warning Letter and Forced Letter both simultaneously have a significant effect and partially have a significant effect toward the positive towards the Effectiveness of Disbursement of Tax Arrears.